United States, directional signs near home in Utqiaġvik - Sorensen, Clarence Woodrow, 1907-1982; Harris, Eugene V., 1913-1978 (1959)
Barrow 52. Modern homes in Point Barrow, Alaska Directional arrow standing before modern homes. Grayscale Sorensen Safety Negatives, Binder: North & Central America 3